Literature Study : Chromosomal Changes in The Class Mammalia Genus Neacomys, Class Actinopterygii Genus characidium, Class Reptile Family Boidae - Nindya Ananda Latifa; Sintia Putri; Elsa Badriyya (Tropical Genetics, 2022)
Chromosomes become an important substance for an organism because they contain information useful for cell regulation and as a hereditary agent. The character of an organism is determined by genes located on chromosomes. Changes in chromosomes will have a significant influence on the evolution of a species. One of the factors that influence changes in chromosomes is mutation. Mutation is a form of defense of an organism in the face of the changing state of nature. Neacomys diversification is caused by gene fusion events, translocations, amplications, and constitutive heterochromatin (CH). In the family Crenuchidae genus Caracidium there was a revision in the diversification of chromosomes 2n of 50 chromosomes composed of 32 metacentric + 18 sub-metacentrics. This is due to differences in the number of rDNA sites, heterochromatin blocks, number of B chromosomes and the size of sex chromosomes, as well as repeated DNA dynamics on chromosomes observed among species forming diversification and chromosomal speciation. In the boidae family reptile class there was a fusion of chromosomes which resulted in the conclusion that the kariotype configuration in snakes is currently the clade of primitive Neotropic snakes.